2022
DOI: 10.1002/ijgo.14128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the COVID‐19 outbreak on transportation of pregnant women in an emergency medical service system: Population‐based, ORION registry

Abstract: The coronavirus disease 2019 , caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), was identified in Wuhan, China in December 2019, after which a COVID-19 outbreak spread rapidly across the world. 1 On March 11, 2020, the World Health Organization (WHO) declared COVID-19 as a pandemic.A previous study has reported that pregnancy was associated with significantly increased chance of hospitalization, ICU admission, and the need for mechanical ventilation due to but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…There was a strong association of difficult-to-transfer cases with patients suspected to have COVID-19 in all age patients, but, interestingly, it was not applicable in children (Table 5). As a previous study showed, hospitals were most likely to accept patients of all ages in the morning (9 am to 10 am), on Fridays, and in the month of June, but this was not applicable to children (Table 5) [11]. In children, the year 2020 was not significantly associated with difficult-to-transfer cases, but the year was significantly associated with hospital admission at the ED (RR 1.14, 95% CI 1.10 to 1.18, P < 0.001), even though children had a reduced RR for hospital admission from the ED (RR 0.51, 95% CI 0.50 to 0.51, P < 0.001) (Supplemental Table 2 and Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 94%
“…There was a strong association of difficult-to-transfer cases with patients suspected to have COVID-19 in all age patients, but, interestingly, it was not applicable in children (Table 5). As a previous study showed, hospitals were most likely to accept patients of all ages in the morning (9 am to 10 am), on Fridays, and in the month of June, but this was not applicable to children (Table 5) [11]. In children, the year 2020 was not significantly associated with difficult-to-transfer cases, but the year was significantly associated with hospital admission at the ED (RR 1.14, 95% CI 1.10 to 1.18, P < 0.001), even though children had a reduced RR for hospital admission from the ED (RR 0.51, 95% CI 0.50 to 0.51, P < 0.001) (Supplemental Table 2 and Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 94%
“…To date, at least to the best of our knowledge, no study has examined emergency transport for obstetrics and gynecology cases on a regional basis. In Osaka, one of the largest cities in Japan, the number of cases of difficulty in transporting pregnant women was lower than that of other cases and remained the same even under pandemic conditions (12).…”
Section: Discussionmentioning
confidence: 92%
“…Children and pregnant women were found to have a negative association with categorization as di cultto-transport cases, but univariate logistic analysis showed greater di culty with hospitals accepting those patients in 2021 compared to 2019, differing from previous studies. 3,4 Each COVID-19 wave in Osaka triggered a medical crisis, where non-COVID-19 medical services such as emergency medicine were temporarily halted, so populations of children and pregnant women might have encountered di culty with transportion. 24 Elderly patients (>65 years of age) were found to have an independent association with increased mortality in the ED.…”
Section: Discussionmentioning
confidence: 99%